Comparison of the effects of 3 different anti-VEGF drugs on cornea thickness, lens thickness and anterior chamber depth - Mehmet Tahir Eski; Kuddusi Teberik; Taha Sezer (Medicine Science, 2023)
To compare the long-term effects of 3 different anti-VEGF molecules on the lens, cornea and anterior chamber in phakic patients who have received consecutive intravitreal injections. 157 patients who did not have corneal pathology but were treated with 1.25mg/0.05ml intravitreal bevacizumab, 0.5mg/0.5ml ranibizumab or 2mg/0.05ml aflibercept injections due to diabetic macular edema were retrospectively analyzed in our clinic. Patients who received three consecutive monthly injections were included to the study. Corneal thickness, lens thickness and anterior chamber depth measurements which were taken before the injections, 1 month after the first injection, 1 month after the second injection, and 1 month after the third injection were used in the study. There was no statistical difference between the bevacizumab, ranibizumab, aflibercept and control group in terms of preoperative specifications such as number of patients, gender and age average. A statistically significant difference was found between the 4 anterior chamber depth measurements in the control group, Ranibizumab drug group, and Bevacizumab and Aflibercept drug groups (p [Med-Science 2023; 12(1.000): 76-80]